Computational Analysis of Catalytic Combustion Using Finite Volume Method (FVM): Advantages, Constraints, and Potential Applications - Muhammad Ahsan; Muhammad Farhan Rafique (Engineering Proceedings)
This study explores the computational analysis of catalytic combustion in cylindrical reactors using the Finite Volume Method (FVM) within Ansys Fluent. Through the incorporation of a combustion channel to facilitate diesel combustion, Ansys Fluent is utilized to predict the fluid dynamics during catalytic combustion. An extensive reaction mechanism file containing all related reactions is added into Ansys Fluent to model the catalytic combustion of methane. In this study, the catalyzed combustion of a methane, hydrogen, and air mixture is simulated on a heated platinum wall within a cylindrical channel using a 2D axisymmetric solver. Two mechanism files are employed: one defining gaseous species and the other including surface species definitions and surface reactions. Volumetric reactions are excluded from this analysis. The cylindrical channel comprises three sections: inlet, catalytic, and outlet, with the catalyzed reactions occurring on the wall surface of the catalytic section. The simulation results exhibit a gradual decrease in the mass fraction of reactants as catalytic combustion proceeds within the chamber, accompanied by a simultaneous increase in product formation. In particular, the presence of a catalytic channel within the combustion chamber catalyzes the combustion reaction, resulting in a higher chamber temperature. This study also presents predicted mass fraction profiles for both reactants and combustion products, highlighting the efficiency of Computational Fluid Dynamics (CFD) simulations in predicting chemical processes, particularly catalytic combustion. This research contributes to the understanding of complex phenomena such as catalytic combustion and underscores the potential of CFD simulations in explaining complicated chemical processes.